Technical feasibility of minicutting of different portions of the branch to produce clonal seedlings of Aloysia citrodora - Thiesen, Leonardo Antonio; Altissimo, Bruna Stringari; Holz, Ezequiel; Pinheiro, Marcos Vinícius Marques; Schmidt, Denise (Comunicata Scientiae, 2022)
Seedling production using the minicutting technique enables quick and efficient plants formation. However, there are no reports of application for Aloysia citrodora (lemon verbena) and the ideal portion of the branch. This study aimed to evaluate the production of seedlings from minicuttings taken from different parts of the branch. The experiment was performed in a completely randomized design. Three treatments consisted of minicuttings taken from other branch portions (basal, median, and apical), divided into two experiments (Exp1 and Exp2). Exp1 was carried out in a sub-irrigation system in phenolic foam, evaluating rooting percentage, length of the longest root, root number, number of shoots, number of leaves, and total dry mass. Exp2 used the minicuttings from the previous experiment, kept for another 35 days in pots to assess the quality of the seedlings, evaluating plant length, number of shoots, and leaves. For Exp1, 35 days after cutting, there was a higher percentage of survival, size of the longest root, number of the root, number of shoots, number of leaves, and total dry mass, in those minicuttings produced from the basal and median portions, being the exact behavior of Exp2, 35 days after transplantation to pots. The minicutting proved to be an efficient method for producing Aloysia citrodora seedlings, when removed from the basal or median portion, standing out for a higher percentage of survival, better growth, and initial development and post-transplantation of the produced seedlings.